P151 Reattendance rates in men presenting with symptoms of urethritis – should we be doing better?. (18th May 2015) - Carter, Naomi; Crofts, Megan; Clarke, Michael; Wheeler, Helen; Sharp, Debbie; Horner, Paddy
Abstract : Background: Chlamydia and gonorrhoea are common causes of urethritis. Management is often based on an enhanced syndromic approach while awaiting results. This can necessitate prescribing to cover a range of potential pathogens, and result in uncertainty for patients. Point of care testing (POCT) for chlamydia and gonorrhoea in men with symptoms of urethritis could alter care pathways and reduce reattendance. Aims: To measure reattendance rates in men presenting with symptoms of urethritis. To identify reasons for reattendance including those that could be mitigated by POCT. Methods: All men with urethritis symptoms presenting over a three month period were identified using electronic patient records. Urethritis was defined as ≥5 pmnls/hpf on a Gram stained urethral smear. Reattendances within 30 days of initial clinic visit and reasons for reattendance were recorded for both microscopy-positive and negative groups. Results: 431 men with urethritis symptoms were identified in a 3 month period. 192 had confirmed urethritis on initial microscopy. 31% of microscopy-positive men and 42% of microscopy-negative men reattended at least once within 30 days of initial visit. Common reasons for reattendance were early morning smear (20%), persistent symptoms (18%), results (16%) and gonorrhoea test of cure (9%). Discussion: This service evaluation has identified high reattendance rates in men with urethritis symptoms. POCT could impact on reattendance rates in a number of ways. Pathogen-guided treatment may reduce antimicrobial failure and persistent symptoms. Same-day results could reduce results visits. Reassurance from negative same-day results may also have a role in reducing persistent symptoms.